Investigation of the effect of exercise applied by video conferencing method on physical fitness in older adult with hypertension - Ozgun Elmas (Medicine Science)
The aim of the study was to examine the effect of exercise applied via video conferencing (VC) method on physical fitness of an older adult with hypertension. The study was conducted with a 68-year-old male older adult case. The patient was exercised using the WhatsApp program using the VC method, 3 days a week, 45 minutes each session, for 12 weeks. Before and after the 12-week exercise program, face-to-face physical fitness evaluations consisting of time-up and go, 6 minute walking test, one-legged standing test and hand grip strength tests were performed on the case. According to the assessment results, improvement was recorded in all physical fitness results of the case with the 12 weeks exercise intervention applied with the VC method. For older adult with hypertension, 12 weeks of exercise using the VC method has been found to be beneficial for improving physical fitness levels. Exercise applied with the VC method may be an alternative to face-to-face exercise practices for older adults with hypertension who cannot access health services. [Med-Science 2025; 14(1.000): 297-9]